2015
DOI: 10.1162/rest_a_00524
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization, Quality, and Export Prices

Abstract: This paper presents theory and evidence from disaggregated Chinese data that tariff reductions induce a country's producers to upgrade the quality of their exports. The paper first documents stylized facts regarding the effect of trade liberalization on export prices.Next, an analytic framework is developed that relates a firm's choice of quality to its access to imported intermediates. In the model a reduction in import tariffs induces a firm to increase export quality and to raise its export price in industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(92 citation statements)
references
References 20 publications
5
86
1
Order By: Relevance
“…It is also unlikely that quality upgrading of exporters is responsible for our results, since higher product quality is associated with higher output prices and production costs (c.f. Kugler and Verhoogen, 2012;Manova and Zhang, 2012;Atkin et al, 2014;Fan, Li, and Yeaple, 2015). This is not compatible with the observed decline in output prices, marginal costs, and the relatively stable input prices in our data.…”
Section: Alternative Interpretations: Input Prices and Product Qualitycontrasting
confidence: 91%
“…It is also unlikely that quality upgrading of exporters is responsible for our results, since higher product quality is associated with higher output prices and production costs (c.f. Kugler and Verhoogen, 2012;Manova and Zhang, 2012;Atkin et al, 2014;Fan, Li, and Yeaple, 2015). This is not compatible with the observed decline in output prices, marginal costs, and the relatively stable input prices in our data.…”
Section: Alternative Interpretations: Input Prices and Product Qualitycontrasting
confidence: 91%
“…This literature has mainly focused on the relationship between importing and productivity and established that the TFP premium from importing intermediate inputs proves to be at least as important as the productivity premium from exporting (Manova and Zhang, 2012;Amiti and Khandelwal, 2013;Fan, Li and Yeaple, 2015). Kasahara and Rodrigue (2008), for example, showed that starting to import intermediate goods led to a productivity increase in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Aw et al (1999) show that average productivity is highest for continuing exporters followed by the group of entrants, exits, and non-exporters. In addition to productivity, market share and product quality are also key determinants driving export prices (Atkeson and Burstein;Manova and Zhang, 2012;Fan, Li and Yeaple, 2014;Bas and Strauss-Kahn, 2015). For example, Fan, Li and Yeaple (2014) show that trade liberalization induce China's producers to upgrade the quality of the goods and raise its export price.…”
Section: Introductionmentioning
confidence: 99%